Localization of the Transpiration Barrier in the Epi- and Intracuticular Waxes of Eight Plant Species: Water Transport Resistances Are Associated with Fatty Acyl Rather Than Alicyclic Components. Issue 2 (7th December 2015) - Jetter, Reinhard; Riederer, Markus
Abstract : The cuticular transpiration barrier is formed by very-long-chain acyls rather than alicyclic wax compounds, primarily in the intracuticular layer and complemented by epicuticular wax in some species. Abstract: Plant cuticular waxes play a crucial role in limiting nonstomatal water loss. The goal of this study was to localize the transpiration barrier within the layered structure of cuticles of eight selected plant species and to put its physiological function into context with the chemical composition of the intracuticular and epicuticular wax layers. Four plant species ( Tetrastigma voinierianum, Oreopanax guatemalensis, Monstera deliciosa, and Schefflera elegantissima ) contained only very-long-chain fatty acid (VLCFA ) derivatives such as alcohols, alkyl esters, aldehydes, and alkanes in their waxes. Even though the epicuticular and intracuticular waxes of these species had very similar compositions, only the intracuticular wax was important for the transpiration barrier. In contrast, four other species ( Citrus aurantium, Euonymus japonica, Clusia flava, and Garcinia spicata ) had waxes containing VLCFA derivatives, together with high percentages of alicyclic compounds (triterpenoids, steroids, or tocopherols) largely restricted to the intracuticular wax layer. In these species, both the epicuticular and intracuticular waxes contributed equally to the cuticular transpiration barrier. We conclude that the cuticular transpiration barrier is primarily formed by the intracuticular wax but that the epicuticular wax layer may also contribute to it, depending on species-specific cuticle composition. The barrier is associated mainly with VLCFA derivatives and less (if at all) with alicyclic wax constituents. The sealing properties of the epicuticular and intracuticular layers were not correlated with other characteristics, such as the absolute wax amounts and thicknesses of these layers.